Strength and Durability of Concrete Incorporating Industrial Wastes, Marine Sand and Seawater Exposed to Marine Environment - Ting, Matthew Zhi Yeon (Curtin University, 2021)
This research investigates the performance of concrete incorporating marine sand, seawater, silicomanganese slag, fly ash and silica fume for application in marine environment. The effect of sulphate attack coupled with wetting-drying action on durability and fatigue behavior of concrete is studied using experimental and numerical methods. Through optimization using statistical analysis, a more sustainable concrete, with better strength and durability than the conventional type, is developed which is suitable for direct industrial use.